(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2023)
Sugar extraction from sugarcane/sugar-beet is an energy-intensive process, both thermal and electrical energies. However, there are numerous opportunities for energy efficiency improvements. A number of tests were conducted in an old sugarcane factory, including the boiler, electricity generation, process, and mill section, to better understand these opportunities. During four years, specific energy consumption was 16-28 GJ/ton of raw sugar. Measurements and calculations revealed that some equipment, e.g. shredder’s steam turbine and some gearboxes, require extensive repairs. The second set of areas for improvement relates to proper operation, such as determining the boiler excess air (which results in an average 0.6% efficiency reduction) and factory planning (near 200 MWh per year). The third type of improvement is to modify or integrate new elements into the existing plant, like water storage tank insulation (3.8 MW) and switching from load-unload operation to drive control for instrumentation compressors (43 MWh). Bangladesh J. Sci. Ind. Res. 58(1), 09-18, 2023